Awaking Awareness of Communication Patterns in The Cyber Radicalism: Covid-19 Pandemic Case Study - Muttaqin, Ahmad; Widyaningsih, Rindha; Riswan, Yulianingsih (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2024)
The high level of internet penetration during a pandemic allows people to be exposed and influenced virtually by radical ideologies. This study aims to provide an overview of the cyber radicalization process and communication patterns during the Covid-19 pandemic. The study utilized the literature review method by reviewing scientific journals, which was accomplished by criticizing, synthesizing, and summarizing the selected data. The results showed that during the Covid-19 pandemic, radical group ideologues spread propaganda via the internet and succeeded in increasing the radicalism sympathize and the number of lone wolves. The radical groups have extraordinary mass communication patterns. They spread radical ideology subtly and greatly influenced the masses. The pattern of intrapersonal communication arises, specifically the internalization of values based on learning, observation, and self-understanding. The radicalism process via the internet is effective media due to its ease, cheapness, and massive and broad spectrum. Straightforward access to radical content found on the internet and social media has led to the emergence of a lone wolf, a person who participates in radicalization by independent process and is not affiliated with any radical groups. This research contributes to completing data on radicalism issues by providing data support in developing strategies to prevent the spread of cyber radicalism.